2017
DOI: 10.1007/s13312-017-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of cryptosporidium in pediatric diarrheal illnesses

Abstract: The high positivity rates during both acute and persistent diarrhea highlights the need to suspect this infection even in immunocompetent children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 107 publications
0
9
1
2
Order By: Relevance
“…Moreover, being malnourished would PLOS NEGLECTED TROPICAL DISEASES mean that the immune system would not adequately protect the child from an opportunistic infection-by Cryptosporidium spp. [33][34][35]. Unfortunately, our cross-sectional study design does not allow us to answer the bi-directional relation between Cryptosporidium spp.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 95%
“…Moreover, being malnourished would PLOS NEGLECTED TROPICAL DISEASES mean that the immune system would not adequately protect the child from an opportunistic infection-by Cryptosporidium spp. [33][34][35]. Unfortunately, our cross-sectional study design does not allow us to answer the bi-directional relation between Cryptosporidium spp.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 95%
“…Although outbreaks of Cryptosporidium in developed countries have been studied in detail, less is known about risk factors for cryptosporidiosis in countries where it is endemic [ 10 ]. Reviews of risk factors for Cryptosporidium infection identified malnutrition, contact with domestic animals, non-exclusive breastfeeding in infants, lack of sanitation facilities, and crowded living conditions as possible risk factors for infection in low- and middle-income countries [ 13 , 14 ]. Few studies have examined risk factors for Cryptosporidium infection in Kenyan children [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, found a positive association between vomiting and cryptosporidiosis [9] [12]. The lack of distinguishable clinical signs or symptoms of cryptosporidiosis in Kibera slums suggests that a detailed examination and screening for this infection should be performed especially in endemic areas [14].…”
Section: Discussionmentioning
confidence: 93%